Using “Engage, Study, Activate" (ESA) Method in Improving Students’ Vocabulary - Susi Astiantih; Bimas Reskiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
AbstractThe researcher discovered that the second-grade students at SMPN 1 Watopute struggled with vocabulary mastering. The teacher reported that several words were not understood by the students during teaching-learning exercises. They were also unable to communicate in English, both orally and in writing, due to a lack of vocabulary competence. As a result, the researcher advised working with the instructor to fix the problem using the Engage, Study, Activate (ESA) strategy. The research topic was "How can the ESA (Engage, Stimulate, Action) strategy increase students' vocabulary acquisition in the second grade of SMPN2Ranteangin?" This was a classroom action research that included the following steps: basic research, planning, action, observing, analyzing, and reflecting in each cycle. The goal of this study is to help students enhance their vocabulary mastery. This study was divided into two rounds. The first cycle was a failure since only 60.8 percent of the students achieved the required score (75). After the second round, 86.9 percent of the students were able to pass the minimal score, indicating that the research was effective. Furthermore, the students demonstrated behavioral gains. They were more engaged in learning and ready to inquire and answer to the teacher. Consequently, the researcher decided to end the research.Keywords: ESA method; improving; mastery; vocabulary.